Follow-up Comparisons of Two Plasma Biomarkers of Alzheimer’s Disease, Neurofilament Light Chain, and Oligomeric Aβ: A Pilot Study - Shim, YongSoo (Current Alzheimer Research, 2023)
Background and Objective: Recent evidence suggests that blood-based biomarkers might be useful for Alzheimer’s disease (AD). Among them, we intend to investigate whether neurofilament light (NfL) and multimer detection system-oligomeric Aβ (MDS-OAβ) values can be useful in screening, predicting, and monitoring disease progression and how the relationship between NfL and MDS-OAβ values changes. Methods: Eighty participants with probable AD dementia, 50 with mild cognitive impairment (MCI), and 19 with subjective cognitive decline (SCD) underwent baseline and follow-up evaluations of the Mini-Mental Status Examination (MMSE) and both plasma biomarkers. Results: Baseline MDS-OAß (p = 0.016) and NfL (p = 0.002) plasma concentrations differed significantly among groups, but only NfL correlated with baseline MMSE scores (r = -0.278, p = 0.001). In follow-up, neither correlated with MMSE changes overall. However, in SCD and MCI participants (n = 32), baseline MDS-OAß correlated with follow-up MMSE scores (r = 0.532, p = 0.041). Linear regression revealed a relationship between baseline MDS-OAβ and follow-up MMSE scores. In SCD and MCI participants, plasma NfL changes correlated with MMSE changes (r = 0.564, p = 0.028). Conclusion: This study shows that only in participants with SCD and MCI, not including AD dementia, can MDS-OAß predict the longitudinal cognitive decline measured by follow-up MMSE. Changes of NfL, not MDS-OAß, parallel the changes of MMSE. Further studies with larger samples and longer durations could strengthen these results.
Keywords: Alzheimer’s disease